2018
DOI: 10.1002/ecs2.2160
|View full text |Cite
|
Sign up to set email alerts
|

Mineral constraints on arctic caribou (Rangifer tarandus): a spatial and phenological perspective

Abstract: Abstract. Arctic caribou (Rangifer tarandus) have the longest terrestrial migration of any ungulate but little is known about the spatial and seasonal variation of minerals in summer forages and the potential impacts of mineral nutrition on the foraging behavior and nutritional condition of arctic caribou. We investigated the phenology, availability, and mechanistic relationships of calcium, phosphorus, magnesium, sodium, potassium, iron, manganese, copper, and zinc in three species of woody browse, three spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 77 publications
(131 reference statements)
0
13
0
Order By: Relevance
“…Juknevičius and Sabienė [ 79 ] had similar results for agricultural plants, indicating that mineral content varied with plant species and Family. Oster et al [ 10 ] demonstrated that even the same species of plant contained different concentrations of minerals over the course of the growing season, depending on location. This demonstrates the complexity of trophic transfer of nutrients beginning at the soil-plant interface within the rhizosphere, which is further complicated by differences among species and the functional responses of the animal to plant growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Juknevičius and Sabienė [ 79 ] had similar results for agricultural plants, indicating that mineral content varied with plant species and Family. Oster et al [ 10 ] demonstrated that even the same species of plant contained different concentrations of minerals over the course of the growing season, depending on location. This demonstrates the complexity of trophic transfer of nutrients beginning at the soil-plant interface within the rhizosphere, which is further complicated by differences among species and the functional responses of the animal to plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing trace minerals in the body of herbivores can be done for the short-term (weeks) by examining plasma samples, or for the long-term (months or years) with liver and bone samples [ 8 , 9 ]. Liver mineral concentrations indicate dietary supplies, as well as the rate of use of liver stores, over a season, which captures the changes in trace mineral concentrations of individual plant species over the growing season [ 10 ]. Liver mineral concentrations may not indicate forage selection of herbivores but ratios of the stable isotopes of carbon (δ 13 C: δ 12 C) and nitrogen (δ 15 N: δ 14 N) can track forage selection in animals [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…What generated these biological associations is unknown, but all these markers were also repeatable among mothers. Temporal variation in nutrient availability partly explains associations among minerals, and between mass gain and minerals found in the forage of migrating caribou (Oster, Barboza, Gustine, Joly, & Shively, 2018). For instance, P and K are associated with photosynthetic parts and decline as plants senesce, while Ca, Fe and Zn are tied to structural components and may increase in concentration with plant senescence (Oster et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Temporal variation in nutrient availability partly explains associations among minerals, and between mass gain and minerals found in the forage of migrating caribou (Oster, Barboza, Gustine, Joly, & Shively, 2018). For instance, P and K are associated with photosynthetic parts and decline as plants senesce, while Ca, Fe and Zn are tied to structural components and may increase in concentration with plant senescence (Oster et al, 2018). Individuals would integrate, through changes in body mass and composition, temporal variation in nutrient content; associations between milk nutrients could similarly be explained, but perhaps only the most stable macro-or micronutrients would show associations at the individual level.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects of mineral imbalances are assumed to occur in wild ungulates and, additionally, imbalances in trace minerals may contribute to population declines [ 1 , 7 , 8 ]. Constraints on dietary trace mineral access by caribou may even influence migration patterns, reproductive success, and calf survival [ 9 ]. Excessive amounts of some trace minerals, as well as heavy metals such as cadmium and lead, are toxic in domestic and wild ungulates, and can cause clinical disease, reduced immune function, and even impaired fecundity and population productivity [ 3 , 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%